Niche assembly of epiphytic bryophyte communities in the Guianas: a regional approach - Sylvia Mota de Oliveira; Hans Ter Steege; Johannes H. C. Cornelissen; S. Robbert Gradstein (Journal of Biogeography, 2009)
Aim Epiphytic bryophyte communities of tropical forests show a gradient in species composition from the base to the top of the host trees, indicating a strong role of niche assembly. This pattern, however, has never been tested at a regional scale. The aim of this study was to test whether niche assembly, rather than dispersal limitation, predominantly drives species composition of bryophyte communities across large spatial scales. Location Three lowland forests in the Guianas: one near Saul, French Guiana; and two near Mabura Hill, Guyana. Methods Communities of epiphytic bryophytes were sampled from six different height zones of several trees in three lowland forests. We analysed the composition of these communities using detrended correspondence analysis in order to find the best explanatory variable for the variation in community composition. A multi‐response permutation procedure was used to test the significance of grouping communities by height zone. We conducted an indicator species analysis to classify species as specialists or generalists and then tested, through weighted averaging, if specialists would indeed maintain their preferred height zone across the Guianas. Results Community composition was explained mainly by height zone. The similarity among communities inhabiting the same height zone of trees, across a distance of up to 640 km, was higher than the similarity among communities established along the vertical gradient of a single standing tree (30–50 m). More than half (57%) of the species had a preferred height zone, and the preference was consistent: species occupied roughly the same height zone on host trees in the different localities. The three local communities investigated were found to belong to the same regional species pool. Main conclusions Throughout the Guianas, epiphytic bryophyte communities are drawn from the same regional species pool, and their composition is shaped by micro‐environmental conditions. The predominance of niche assembly over dispersal assembly rules is consistently found at both local and regional scales.